Maintenance of international peace and security: analysis of Russian use of force abroad and Article 39 of UN Charter implementation in Georgia in 2008 - Bēta, Sindija (Riga Graduate School of Law, 2019)
The paper examines Article 39 of the UN Charter and how the main principle of the Security Council “to maintain or restore international peace and security” is interpreted by Russia and is it consistent with the understanding established by the international community and UN itself. To understand the Russian approach towards the principle, Georgian conflict of 2008 is chosen to analyze how Russia implemented this principle in a crisis scenario and can the particular use of force case fall under Article 39 norms. Paper aims to show the differences between Article 39 cases in Kosovo and Libya and Russian intervention in Georgia to emphasize how Russian understanding of Article 39 is based on national interests and limits their neighbouring states’ rights under UN Charter. It is argued here that Russia has illegally defined its zones of interest, whilst limiting the operational capacities of the UN Security Council.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Russian Federation; United Nations Security Council